Malicounda-Bambara - The Sequel : Journey of a Local Revolution - Easton, Peter; Monkman, Karen (World Bank, Washington, DC, 2012)
The note explores the dimensions of the initiative to abandon the practice of female genital cutting (FGC), which begun in Senegal, and spread nationwide, and to several other African countries. This initiative took part in a non-formal education program, sponsored by a Senegal-based nongovernmental organization, "Tostan", a program focused on themes of women's health, and human rights, and the beginnings of literacy. During the training program, women shared their experiences on this taboo topic, and confronted them with a new sense of women's rights, by approaching local authorities, and community members to win support for a declaration of intent to abandon this practice. The statement renouncing the practice, made in July 1997, made a minor media impact, though in local culture it did have greater impacts, despite some opposition. Regardless of the controversy, the spread of the initiative reached a turning point, when a religious leader became supportive of this cultural change, which led to the development of a strategy. Essentially, the strategy strength was based on its collective nature, on the fact that it came across as a movement for internal consistency, and liberation, not as an outside condemnation, and, it was an empowering method, i.e., its resolution was left to the initiative of each community, and its members.